1989
DOI: 10.1126/science.2570460
|View full text |Cite|
|
Sign up to set email alerts
|

Identification of the Cystic Fibrosis Gene: Genetic Analysis

Abstract: Approximately 70 percent of the mutations in cystic fibrosis patients correspond to a specific deletion of three base pairs, which results in the loss of a phenylalanine residue at amino acid position 508 of the putative product of the cystic fibrosis gene. Extended haplotype data based on DNA markers closely linked to the putative disease gene locus suggest that the remainder of the cystic fibrosis mutant gene pool consists of multiple, different mutations. A small set of these latter mutant alleles (about 8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
746
2
38

Year Published

1990
1990
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 3,570 publications
(796 citation statements)
references
References 40 publications
10
746
2
38
Order By: Relevance
“…Cystic fibrosis (CF) is caused by mutations of the Cystic Fibrosis Transmembrane Conductance Regulator (CFTR) [1-3] and constitutes with 1 case per 2500 births the most common autosomal recessive disorder in the EU and the USA. Approximately 40 000 children and young adults are affected in the EU.…”
Section: Cystic Fibrosismentioning
confidence: 99%
“…Cystic fibrosis (CF) is caused by mutations of the Cystic Fibrosis Transmembrane Conductance Regulator (CFTR) [1-3] and constitutes with 1 case per 2500 births the most common autosomal recessive disorder in the EU and the USA. Approximately 40 000 children and young adults are affected in the EU.…”
Section: Cystic Fibrosismentioning
confidence: 99%
“…Mutations in this gene cause cystic fibrosis, which is one of the most common inherited genetic life-shortening diseases, reducing the life expectancy to 37.5 years, across different populations. 74 Two particular mutations, ∆F 508 the most common CFTR mutation (70% and 90% of cystic fibrosis cases in U.K. and U.S., respectively) and 1653C/T a relatively rare single point mutation occurring in the same gene fragment, were targeted. We show that we can distinguish between the wild type, the single nucleotide mutation, and the most common triplet deletion in the human CFTR gene by employing SER(R)S to follow melting of the dsDNA from the SSV surface as either the temperature or the applied potential is scanned.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies demonstrated that CF is caused by mmations in the gone coding for a transmembrahe protein denominated Cystic Fibrosis Transmembrane conductance Regulator, CFTR [2][3][4]. Transfeetion experiments [5][6][7] and the functional reconstitution into liposomes [8] demonstrated that CFTR is indeed a cAMP-dependent chloride transporter.…”
Section: Introductionmentioning
confidence: 99%